Nurses and nursing : the person and the profession - Ó Lúanaigh, Pádraig, MSc(Psych) (Online access with DDA: Askews (Medicine), 2017)
This textbook draws on international contributors with a range of backgrounds to explore, engage with and challenge readers in understanding the many aspects and elements that inform and influence contemporary nursing practice.